Pengaruh Hasta Karya Miniatur Alat Kebersihan dalam Meningkatkan Kreativitas Seni di Taman-Kanak Sadar Bahkti Kecamatan Talamau - Dwiva Rahma Lisa; Dadan Suryana; Nenny Mahyudin (Journal on Education, 2023)
One of the forms of works of art is hasta works or crafts. Art activities play an important role in many aspects of child development, including the development of creativity in early childhood. Creativity is human interaction with the environment to create imaginative methods and products that have benefits in solving problems. Children's creativity can grow and develop optimally if the learning environment is supported by the provision of various media. The purpose of this study was to find out whether the hurdles of miniature cleaning tools have an effect on increasing artistic creativity in early childhood. The research method used is quasi-experimental with experimental design. The sample consisted of students in grades B1 and B2, each of which had 17 children. The data collection technique used in this study was an action test (t. test) for differences. Based on the results of the study that the work of hasta works of miniature cleanliness affects artistic creativity and trains ideas, motivates children and helps children to be interested in participating in the learning process.